PENGEMBANGAN MEDIA INTERAKTIF QUIZIZZ BERBASIS LITERASI DIGITAL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS IV - Diyarotun Nahara; Novialita Angga Wiratama (Prodi PGSD Universitas PGRI Ronggolawe, 2023)
The rapid development of technology has brought about convenience in various aspects. Especially in the field of education, which can provide convenience for educators and learners. A technology in education can be implemented in the utilization of instructional media as a tool to facilitate the achievement of learners' learning outcomes. Through technology-based instructional media, educators can provide convenience and practicality in conveying insights during a learning process. This study employs the ADDIE study methodology, which comprises five stages: analyze, design, development, implementation, and evaluation. From the validation results, the following percentages were obtained: content experts with 96%, media experts with 88%, and language experts with 95%. In the effectiveness test, the data of fourth-grade students at Sumurpule Elementary School were obtained. Prior to the intervention, the average score was 52, and following the intervention, the average score increased to 82. Additionally, the attractiveness assessment yielded a percentage score of 95%. From the validation testing, it can be concluded that the product can be used without revisions. In the effectiveness test, the final scores showed an improvement, indicating that the product is effective for use. In terms of attractiveness, it achieved a percentage of 95%, signifying that the product is highly appealing.